Development of Pluronic® nanocarriers comprising Pheophorbide, Zn-Pheophorbide, Lapachol and β-lapachone combined drugs: Photophysical and spectroscopic studies. (October 2018) - Campanholi, Katieli da S.S.; Gerola, Adriana P.; Vilsinski, Bruno H.; de Oliveira, Évelin L.; de Morais, Flávia A.P.; Rabello, Bruno R.; Braga, Gustavo; Calori, Italo R.; Silva, Expedito L.; Hioka, Noboru; Caetano, Wilker
Abstract: Therapy efficiency is ruled by a single agent, which can be enhanced using an adjuvant, increasing cell inhibition in a synergetic aspect. Taking this into account, the photosensitizers Pheophorbide and Zinc-Pheophorbide, and their physical chemical and photodynamic properties, were evaluated with Lapachol and β-lapachone drugs. They were incorporated into triblock copolymers P123 and F127 as biocompatible nanocarriers. Spectrophotometric studies showed photosensitizer monomerization in the combined formulation, a fundamental aspect for optimal photodynamic results. The apparent pKa studies of Lapachol incorporated in copolymeric micelles indicated small variations when compared to the data in a homogeneous medium (water/ethanol). This demonstrated the composition of 76% and 56% for deprotonated forms of Lapachol at the physiological pH, after administration of the formulated systems in F127 and P123, respectively. This preferential location is in the poly (ethylene oxide) interfacial bulk of the Pluronic ® . The characterization of the photophysical properties of the combined systems showed an expressed decrease of fluorescence quantum yield of the PS in the β-lapachone based systems. This was attributed to greater suppression by collisions with water molecules due to variations in the accommodation region of the photosensitizer after simultaneous encapsulation. The combined system showed a decrease of singlet oxygen quantum yield due to high local micellar microviscosity and low molecular oxygen concentration. However, a five-fold increase in singlet oxygen lifetime was noted in systems within the nanostructured microenvironment, which enhances the range of photosensitizer action. The combined system showed marked thermal stability when subjected to refrigeration, which was below the critical micellar temperature for nanocarriers. This was true after subsequent reheating as well. In addition, the formulations were stored for prolonged periods in the lyophilized state that demonstrated the maintenance of the monomeric state of the photosensitizers. This is a desirable effect for photodynamic applications. The majority of the combined systems incorporated into the nanostructured microenvironment showed temporal stability for more than 96 h in an aqueous solution. Graphical abstract: Photosensitizers (PS) and Naphthoquinones (Napht) are incorporated into nanocarriers. The mechanism of the PS action associated with Naphthoquinones, responsible for the formation of singlet oxygen and reactive oxygen species, will allow for treatment optimization and an increase in the rate of cell death. Highlights: The studies showed the monomerization of Pheophorbide and Zinc-Pheophorbide photosensitizers, even after the simultaneous incorporation of Lapachol and β-lapachone naphthoquinones in micellar nanostructured carrier systems. Studies of apparent pKa of lapachol and self aggregation effects allowed for significant spectral variations after incorporation into the micellar nanostructured system, either single or in combination with photosensitizers. Changes in the microenvironment of the photosensitizer after simultaneous incorporation led to a reduction in the fluorescence quantum yield of the photosensitizers combined with β-lapachone. The combined system showed a five-fold increase in the lifetime of the singlet oxygen produced by Pheophorbide and Zinc-Pheophorbide, which increases the radius of action due to diffusion of singlet oxygen.